AN OTHER APPROACH FOR THE PROBLEM OF FINDING A COMMON FIXED POINT OF A FINITE FAMILY OF NONEXPANSIVE MAPPINGS - Tuyen, T. M. (Journal of Nonlinear Analysis and Optimization: Theory & Applications (JNAO), 2012)
The purpose of this paper is to give a Tikhonov regularization method and some regularization inertial proximal point algorithm for the problem of finding a common fixed point of a finite family of nonexpansive mappings in an uniformly convex and uniformly smooth Banach space E, which admits a weakly sequentially continuous normalized duality mapping j from E to E*.